2016
DOI: 10.1186/s12889-016-3491-1
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood maltreatment as a risk factor for diabetes: findings from a population-based survey of Canadian adults

Abstract: BackgroundIt is well established that childhood maltreatment (CM) is a risk factor for various mental and substance use disorders. To date, however, little research has focused on the possible long-term physical consequences of CM. Diabetes is a chronic disease, for which an association with CM has been postulated.MethodsBased on data from a sample of 21,878 men and women from the 2012 Canadian Community Health Survey - Mental Health (CCHS - MH), this study examines associations between three types of CM (chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 48 publications
(69 reference statements)
1
40
2
Order By: Relevance
“…As the present data combine results for men and women, this may explain the discrepant results. Regarding the association between diabetes and sexual abuse, the ORs presented here are comparable in size to those in the analyses of Shields, Hovdestad, Pelletier et al (2016). …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…As the present data combine results for men and women, this may explain the discrepant results. Regarding the association between diabetes and sexual abuse, the ORs presented here are comparable in size to those in the analyses of Shields, Hovdestad, Pelletier et al (2016). …”
Section: Discussionsupporting
confidence: 81%
“…The pivotal role for sexual abuse, which was seen for the association between COPD and diabetes in the analyses by Shields and colleagues (Shields, Hovdestad, Gilbert et al, 2016; Shields, Hovdestad, Pelletier et al, 2016), was not confirmed in the present data. Nevertheless, in their analyses regarding COPD, results were presented stratified for gender, with markedly higher ORs for women compared to men, for whom no significant association was demonstrated (Shields, Hovdestad, Gilbert et al, 2016).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Interestingly, childhood trauma has been associated with several clinical variables that are likely to be associated with poor lithium response, such as early onset, mixed features, rapid cycling and substance misuse . Moreover, childhood trauma has been associated with numerous medical conditions, such as obesity , cardiovascular diseases, asthma, gastric ulcers, migraine, arthritis , metabolic risk markers or diabetes . Some of these somatic conditions were in turn associated with poor response to lithium as mentioned above.…”
Section: Introductionmentioning
confidence: 99%